Differentiated Learning Strategies by Guru Penggerak: Accommodating the Needs of Slow Learner in Primary School - Yusrika Firda Isnaini; Minsih Minsih; Choiriyah Widyasari; Helzi Helzi (STAI Hubbulwathan Duri, 2025)
Slow learners are students with below-average cognitive abilities who require more time and support to grasp academic concepts. Their learning challenges often include difficulties in reading, writing, and comprehending instructional content, resulting in delayed task completion and lower academic performance. Addressing these needs is crucial within inclusive classrooms, especially under the Indonesian Guru Penggerak (Teacher Leader) program, which aims to foster transformative, student-centered learning.This qualitative study explores how a Guru Penggerak implements differentiated learning strategies to support slow learner students in a second-grade inclusive classroom at SDN Kadokan 02. Data were collected through classroom observations, semi-structured interviews with the teacher and principal, and analysis of relevant documents. Data triangulation was used to ensure validity, and analysis followed the steps of data reduction, presentation, and conclusion drawing.Findings indicate that the teacher implemented two core differentiation strategies: process differentiation—providing guided instruction, visual media, and individualized support—and product differentiation—modifying assessment formats to align with students’ readiness levels. Regular students engaged in more independent learning, while slow learners received intensive scaffolding through visual aids, repeated instructions, and individualized feedback.The differentiation approach effectively addressed diverse readiness levels within the same classroom, supporting both slow learners and their peers. The role of the Guru Penggerak was critical in designing inclusive and adaptive learning processes.Differentiated instruction, as practiced by Guru Penggerak, is an effective strategy to accommodate slow learners in inclusive classrooms. This study offers practical insights for educators aiming to implement equitable teaching strategies.